CholecTriplet2022: show me a tool and tell me the triplet - an endoscopic vision challenge for surgical action triplet detection - Nwoye, Chinedu; Yu, Tong; Sharma, Saurav; Murali, Aditya; Alapatt, Deepak; Vardazaryan, Armine; Yuan, Kun; Hajek, Jonas; Reiter, Wolfgang; Yamlahi, Amine; Smidt, Finn-Henri; Zou, Xiaoyang; et al. (Medical image analysis, 2023)
Formalizing surgical activities as triplets of the used instruments, actions performed, and target anatomies is becoming a gold standard approach for surgical activity modeling. The benefit is that this formalization helps to obtain a more detailed understanding of tool-tissue interaction which can be used to develop better Artificial Intelligence assistance for image-guided surgery. Earlier efforts and the CholecTriplet challenge introduced in 2021 have put together techniques aimed at recognizing these triplets from surgical footage. Estimating also the spatial locations of the triplets would offer a more precise intraoperative context-aware decision support for computer-assisted intervention. This paper presents the CholecTriplet2022 challenge, which extends surgical action triplet modeling from recognition to detection. It includes weakly-supervised bounding box localization of every visible surgical instrument (or tool), as the key actors, and the modeling of each tool-activity in the form of ‹instrument, verb, target› triplet. The paper describes a baseline method and 10 new deep learning algorithms presented at the challenge to solve the task. It also provides thorough methodological comparisons of the methods, an in-depth analysis of the obtained results across multiple metrics, visual and procedural challenges; their significance, and useful insights for future research directions and applications in surgery.